Características morfométricas e suas implicações no acúmulo de sedimentos em reservatórios: O Caso Da Represa Hedberg, IPERó/SP. - Da Cunha e Silva, Darllan Collins [UNESP]; Sales, Jomil Costa Abreu [UNESP]; Filho, José Luiz Albuquerque; Lourenço, Roberto Wagner [UNESP] (My University, 2016)
Sediments resulting from erosion are a silting major contributor, in many cases, causing aquatic environments eutrophication. Thus, this study evaluated spatially the degradation degree of a reservoir, by physicochemical evaluation, limnological, as well as hydrological and hydraulic modeling, aiming the problem characterization and diagnosis as a subsidy tool to mitigating actions. The results showed that the water reservoir has a substantial water volume around 500,000 m3 and a 2.28 perimeter development index, indicating a margins moderate irregularity degree. The reservoir bottom relief showed the deepest areas in the guidance of west-central to northeast and from northeast to north, being the deepest region is around 120 m from the dam, with average and maximum slope of approximately 30% and 52%. The limnetic and coastal region conductivity and temperature were above the tolerance levels suggested by the environmental agency indicating a large amount of dissolved ions, which may come from sewage or soil erosion. It was also possible to identify the algae and macrophytes proliferation, which may indicate the presence of hypertrophication process. For the qualitative improvement of the reservoir, dredging interventions and restoration of riparian vegetation in the dam surroundings areas should be performed, thus improving water quality conditions. The methodology proved to be very efficient to quantify sediment in reservoirs and great relevance to managing programs development and reservoirs management.
Morphometric characteristics and implications in sediment accumulation in reservoirs: The case of Hedberg Dam, Iperó / SP.
Keywords: Erosion; Reservoirs; Sediments; Water quality